FETAL MUMMIFICATION IN A COW -A CASE REPORT - Chaudhary, S R; Shrawankar, P R; Siddiquee , G M (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A case of mummification of fetus in a crossbred cow which is a rare gestational disorder has been placed on record.